2011
DOI: 10.5194/hess-15-311-2011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate evolution and land use changes on water yield in the ebro basin

Abstract: Abstract. In this study the climatic and hydrological trends across 88 sub-basins of the Ebro River basin were analyzed for the period . A new database of climate information and river flows for the entire basin facilitated a spatially distributed assessment of climate-runoff relationships. It constitutes the first assessment of water yield evolution across the whole Ebro basin, a very representative example of large Mediterranean rivers. The results revealed a marked decrease in river discharges in most of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(114 citation statements)
references
References 49 publications
3
104
0
7
Order By: Relevance
“…Este cambio coincide precisamente con el momento en que se manifiesta de manera más acusada la recolonización vegetal tras el abandono del cultivo en laderas y el descenso de los incendios de origen humano. En un estudio más amplio sobre la evolución de los caudales en la cuenca del Ebro, López- Moreno et al (2011b) comprobaron la ocurrencia de un marcado descenso de los caudales en la mayoría de las subcuencas. La evolución temporal de los residuales de modelos empíricos que relacionan el clima y la escorrentía en cada subcuenca proporcionaron evidencias de que el clima por sí solo no puede explicar el descenso observado en el caudal, si no se tiene en cuenta el aumento de la evapotranspiración por la vegetación natural, asociada al abandono de tierras de cultivo y al descenso de la presión ganadera.…”
Section: Las Consecuencias Del Cambio Global Sobre Los Recursos Hídriunclassified
See 1 more Smart Citation
“…Este cambio coincide precisamente con el momento en que se manifiesta de manera más acusada la recolonización vegetal tras el abandono del cultivo en laderas y el descenso de los incendios de origen humano. En un estudio más amplio sobre la evolución de los caudales en la cuenca del Ebro, López- Moreno et al (2011b) comprobaron la ocurrencia de un marcado descenso de los caudales en la mayoría de las subcuencas. La evolución temporal de los residuales de modelos empíricos que relacionan el clima y la escorrentía en cada subcuenca proporcionaron evidencias de que el clima por sí solo no puede explicar el descenso observado en el caudal, si no se tiene en cuenta el aumento de la evapotranspiración por la vegetación natural, asociada al abandono de tierras de cultivo y al descenso de la presión ganadera.…”
Section: Las Consecuencias Del Cambio Global Sobre Los Recursos Hídriunclassified
“…Diferentes estudios han confirmado un descenso estadísticamente significativo en los caudales anuales (por supuesto, en ríos no alterados por embalses o por derivaciones de agua) López-Moreno et al, 2011b, 2014, y un adelanto en aproximadamente un mes del momento en que se produce el máximo primaveral (Ló-pez- . Naturalmente, esto introduce cambios en la gestión de los embalses, que cada vez más se ven obligados a almacenar agua de forma constante desde octubre o noviembre hasta junio, cuando hace tan sólo 20 años casi se paralizaba el llenado de los embalses durante el invierno (López- .…”
Section: Discusión Y Conclusionesunclassified
“…Hydrologically, the growth of vegetation directly affects interception, infiltration, evapotranspiration and soil storage of water, usually reducing runoff production and peak flows (López-Moreno et al, 2008;Lana-Renault et al, 2011). Vegetation expansion also causes a shrinkage of sediment sources (Bakker et al, 2008;Lana-Renault and Regüés, 2009) and a decrease in sediment supply from hillslopes to channels (Piégay et al, 2004;Quiñonero-Rubio et al, 2016), reducing the sedimentation levels of reservoirs, rivers and coastal areas (Keesstra, 2007;López-Moreno et al, 2011) and altering stream morphology, including the narrowing and incision of alluvial plains (Beguería et al, 2006;Sanjuán et al, 2016). The mechanisms by which changes in a landscape (e.g., due to farmland abandonment) affect the transfer of water and sediment through a drainage basin are a "hot topic" of hydrological and geomorphological research and have led to the increased use of the concept of hydrological connectivity.…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 99%
“…Mean annual inflow into the Miyun Reservoir declined from 88.2 m 3 s −1 in the 1950s to 15.8 m 3 s −1 in the 1980s (Gao et al, 2002). Meanwhile, population in Beijing increased from 2.8 million in 1953 to 20 million in the 2000s (Liu et al, 2003). The local water consumption in the catchment is believed to be the main driving factor in addition to climate (Ma et al, 2010).…”
mentioning
confidence: 99%
“…For example, Wang et al (2009) and Ma et al (2010) suggested that climate impact separately accounted for about 33 and 55 % of the decrease in reservoir inflow using the distributed time-variant gain model and geomorphology-based hydrological model, respectively. The discrepancies are mainly caused by assessment methodology due to parameter uncertainty (Shen et al, 2012), diversities of structural complexity (Velázquez et al, 2013), and inconsistencies of the evaluation period (López-Moreno et al, 2011). It remains a grand challenge in watershed hydrology (especially for large basins) to seperate the hydrological effect of land use and from climate change and variability.…”
mentioning
confidence: 99%